A pilot study of intraoperative melphalan to prevent recurrent PVR: the IOMPVR study - Carlos A. Moreira-Neto; Jose S Pulido; Luca Bongiovanni de Miranda Gonçalves; Gabriel Nunes Cavalcanti; Acacio Souza Lima; José de Paula Barbosa Neto; Daniel Lavinsky; Talita Virginia Fernandes de Oliveira; Fernando Ejii Ogata; Lucas Zago Ribeiro; Luiz Fernando Teixeira; Flavia Borelli Gomes do Nascimento; et al. (International Journal of Retina and Vitreous)
Abstract Background Proliferative vitreoretinopathy (PVR) is a major cause of failure in cases of retinal detachment (RD) repair. Intravitreal melphalan, a known inhibitor of cellular proliferation, offers a novel therapeutic approach to reduce PVR recurrence and improve outcomes. We evaluated the safety and efficacy of 5 µg/0.1 ml intravitreal melphalan at the end of pars plana vitrectomy (PPV) before silicone oil (SO) injection in eyes with primary PVR related to rhegmatogenous retinal detachments (RRDs) with a minimal 90-day follow-up period. Methods This prospective, cross-sectional, interventional pilot study was conducted at the Department of Ophthalmology of the Federal University of São Paulo in patients with primary RRD and PVR. Patients were included who were aged 18 to 85 years with PVR grade CP2 or worse secondary to RRDs in eyes without having undergone a previous RRD surgery. They underwent PPV + scleral buckle + fluid air exchange followed by intravitreal injection of 5 µg/0.1 ml melphalan (270 mOsm) and SO injection. Results Six eyes of six patients were enrolled. Ocular examination and imaging showed no retinal toxicity. The logarithm of the minimum angle of resolution best-corrected visual acuity improved from the mean ± standard deviation preoperatively of 2.11 ± 0.22 to 0.89 ± 0.37 at 30 and to 0.84 ± 0.42 at 90 days postoperative (P < 0.001). Optical coherence tomography identified intraretinal cysts in five of six eyes and outer retinal layer loss in all study eyes. Only one of six eyes developed a recurrent localized RD on day 90 unrelated to recurrent PVR. PVR recurrence was not observed during the study follow-up. Conclusions In this pilot study, the preliminary data showed that PPV followed by intravitreal injection of 5 µg/0.1 ml melphalan was not related to ocular toxicity. The absence of PVR recurrence at 3 months follow-up in these complex PVR eyes is an interesting finding that justifies further investigation.